16. SCORE-UC: Antibiotic Stewardship in Urgent Care. (31st December 2020) - Hersh, Adam; Stenehjem, Eddie; Fino, Nora; Willis, Park; Srivastava, Rajendu; Buckel, Whitney R; Brunisholz, Kim; Wallin, Anthony; Kumar, Naresh; Samore, Matthew H
Abstract: Background: Urgent care (UC) is a rapidly growing site of healthcare delivery. The CDC developed Core Elements for Outpatient Antibiotic Stewardship to guide development of outpatient stewardship but little experience exists in applying Core Elements to UC settings. Our objective was to evaluate the effectiveness of a UC stewardship program in a health system. Figure Methods: We designed a UC stewardship program for Intermountain Healthcare's 39 UC sites based on CDC Core Elements. The pre-intervention period was Aug 2017-June 2019. The intervention period was 12 months from Jul 2019 -June 2020. The program consisted of education for patients/providers about appropriate diagnosis and prescribing for respiratory conditions; media campaigns; EHR tools; and a prescribing dashboard for clinicians. The primary outcome was the percentage of respiratory visits where an antibiotic was prescribed. Secondary outcomes included the percentage of encounters receiving antibiotics for conditions where no antibiotics are indicated (e.g. bronchitis) and the percentage of encounters receiving first-line recommended therapy for conditions in which antibiotics may be warrented (otitis media, sinusitis, and pharyngitis). We used a binomial mixed effects hierarchical model to calculate the odds of antibiotic prescribing associated with the intervention period accounting for pre-intervention trends. Models account for clustering within providers and clinics. We present the results of an interim analysis after 7 months of the intervention. Results: The overall number of UC encounters during the study period was 1, 559, 403 and 41.5% were for respiratory conditions. The percentage of patients with respiratory conditions that received an antibiotic prescription declined from 49.9% pre-intervention to 35.3% during the intervention (OR 0.73, 95% CI: 0.71, 0.76), reaching a low of 30% during February 2020 (Figure). Prescribing for conditions where antibiotics are not indicated decreased (OR 0.31, 95% CI 0.26–0.36) and first line recommended therapy increased (OR 1.28, 95% CI 1.20–1.26) during the intervention. Conclusion: After 7 months of a planned 12 month intervention, the UC stewardship program was associated with improved antibiotic prescribing. Disclosures: Rajendu Srivastava, MD, AHRQ, NIH, CDC (Grant/Research Support, I hold grants from AHRQ, NIH and CDC for a variety of clinical research and implementation studies)IPASS Patient Safety Institute (Other Financial or Material Support, I am a physician founder of this company to spread handoff best practices and reduce adverse events. My employer holds my equity in this company.)